A fatal feast : a murder, she wrote mystery : a novel - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote., 2010)
The newest novel in the "USA Today" bestselling series finds Jessica Fletcher cooking up a heartwarming holiday dinner--and a fresh serving of trouble as she and Inspector George Sutherland take a post-turkey stroll in Cabot Cove, Maine, and stumble upon the body of a man with a carving knife stuck in his chest.